Study of the alteration of gustatory perception in users of antidepressant drugs - Juliane Angelica Reges Almeida; Jamille Marinho Brazil; Talita Batista Matos; Lucas Almeida Silva; Maria Patrícia Milagres (O Mundo da Saúde, 2017)
The use of antidepressant drugs has increased alarmingly in society, it is noteworthy that some drugs when used chronically and / or associated with other drugs may result in changes in taste. The palate provides essential information about the food, avoiding, for example, the intake of food unfit for consumption. In this context, this study aimed to verify the taste sensitivity users of antidepressant medications, measuring the threshold index for sweet and salty tastes. The survey was conducted with 80 individuals, 40 users of antidepressant medications and other nonusers of antidepressants. In the study group, we applied a structured sociodemographic and lifestyle questionnaire, conducted a nutritional assessment, and analyzed the medical records concerning medication use. The evaluation of sensitivity was performed by the taste perception threshold test, i.e., the rapid method of type-3 Alternative Forced Choice for the test and control group. It was observed that the perception of sweet and salty tastes limits are increased in users of antidepressant drugs compared to the control group, showing significant difference between the threshold levels of the groups. Therefore, it was noted that users of antidepressant medications by determining the threshold index, have a lower sensitivity to taste sweet and salty tastes.